1998
DOI: 10.1080/15513819809168791
|View full text |Cite
|
Sign up to set email alerts
|

The Colostrum-Deprived, Artificially Reared Neonatal Pig as a Model Animal for Studying Rotavirus Gastroenteritis

Abstract: H i l l and Raleigh, N o r t h Carolina, USA 0 Rotavirus gastroenteritis is one of the main causes of acute diarrhea in young humans and animals worldwide. T h e colostrum-deprived, artificially reared neonatal pig has been extensively used in our laboratov as a model animal f o r studying an experimentally induced rotaviral gastroenteritis. Details on procurement of newborn pigs, immunologic characteristics, and artificial rearing conditions of colostrumdeprived neonatal pigs as well as on rotavirus inoculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The piglets were fed a commercial pig milk replacer d based on a previously described regimen. 7 Intervals between feeding and observations of the piglets were never longer than 4 hr. The piglets were handled in accordance with the guidelines set forward in The Guide to the Care and Use of Experimental Animals of the Canadian Council on Animal Care.…”
Section: Methodsmentioning
confidence: 98%
“…The piglets were fed a commercial pig milk replacer d based on a previously described regimen. 7 Intervals between feeding and observations of the piglets were never longer than 4 hr. The piglets were handled in accordance with the guidelines set forward in The Guide to the Care and Use of Experimental Animals of the Canadian Council on Animal Care.…”
Section: Methodsmentioning
confidence: 98%
“…Clinical disease may occur in the postweaning period or, less frequently, in the neonatal pig, with the symptoms of diarrhea, vomiting, enterocolitis, and bacteremia (with major organ involvement in more severe infections). Therefore, the young pig is a desirable target for vaccination and is also a good model for human gastroenteritis (20,48).…”
mentioning
confidence: 99%
“…In Europe, Salmonella serovar Typhimurium is the serovar that is most frequently isolated from humans or pigs (25), while in the United States it is estimated that up to 4 million cases of salmonellosis occur annually, of which about 500 are fatal (19). Although vaccination of piglets against Salmonella is a desirable target, gnotobiotic piglets have previously been shown to be a useful model of enteric disease in humans (16,20,41). Recently, we showed that oral inoculation of 5-day-old gnotobiotic piglets with a rough lipopolysaccharide (LPS) mutant of S. enterica serovar Infantis 1326/28 (1326/28⌽ r ) protects against a subsequent, normally lethal challenge with Salmonella serovar Typhimurium strain F98 (16).…”
Section: Preinoculation Of Susceptible 5-day-old Gnotobiotic Piglets mentioning
confidence: 99%